The neoliberal syndemic: critical narratives and struggles from southern Europe - Espinoza Pino, Mario; Meloni González, Carolina (Política y Sociedad, 2024)
The social impact of the outbreak and spread of the COVID–19 pandemic has shown that we’re not facing a mere infectious disease, but a neoliberal syndemic. This syndemic have stressed all the inequalities, oppressions and conflicts that were at the base of the neoliberal system of governance, contradictions that have reached a global dimension since the Great Recession (2008). In this article we will analyze the consequences of the neoliberal virus in different spheres (macro and micro) from a critical and materialistic perspective: from the management of the crisis by the States to the subjective transformations the syndemic has provoked in the population. Focusing in the Spanish case, we will go over the main reactions, narratives and struggles that have faced the Covid crisis into what we understand as a new and more authoritarian phase of neoliberal capitalism. A phase that will need a radical articulation of social struggles to subvert a horizon that threatens with new oppressions.
Keywords: COVID-19; neoliberalism; syndemic; Marxism; intersectionality; social struggles